OPTIMIZING EDUCATIONAL OUTCOMES: EXPLORING INNOVATIVE APPROACHES IN CONTEMPORARY PEDAGOGY - Abdurahman, Ayi (Jurnal Review Pendidikan dan Pengajaran, 2024)
This study aims to explore a range of innovative approaches in contemporary pedagogy, focusing on optimizing educational outcomes. In the context of rapid global change and technological advancement, the study details innovative concepts, such as technology integration, learning differentiation, flipped classrooms, and project-based learning, to identify their impact on student engagement and academic achievement. Qualitative research methods are used through in-depth interviews and direct observation at various levels of education, from elementary school to college. The results show that integrating technology into learning can provide a more dynamic learning experience while learning differentiation supports student diversity. Innovative approaches in higher education, such as flipped classrooms and project-based learning, also open up opportunities to increase student engagement. Emerging challenges involve the availability of resources, teacher training, and resistance to change. In conclusion, this study emphasizes the importance of a holistic and adaptive approach in achieving optimal educational outcomes in this contemporary era. The practical implications of this research can help policymakers, educators, and education practitioners develop more effective and inclusive strategies.